Knjiga Eksodus v srednjeveških hrvaškoglagolskih brevirjih in misalih - Stankovska, Petra (Slavistična revija, 2018)
Most of the text of the Book of Exodus preserved in medieval Croatian Glagolitic liturgical books is found in missals (readings of variable length from chapters 12 to 32) and a relatively brief text from this book is included in breviaries (readings from chapter 3 and beginning of 4 in full). In spite of this, there are unique parts of this book in the breviary of Vid of Omišalj, with no or almost no parallels in other known breviaries-chapters 1 and 2 in full, and chapters 5 to 15, some in full and some paraphrased. The article deals with basic textual analysis of the Biblical text from the book of Exodus preserved in medieval Croatian Glagolitic liturgical books, comparing it with the Old Church Slavonic translations of Biblical sites found in the books of Slavia Orthodoxa.
Keywords: biblija; Eksodus; parimejnik; prevodi; stara cerkvena slovanščina